Ousar Lutar. Ousar Vencer. Órgão do Movimento Associativo dos Estudantes de Direito de Lisboa (1973)
Ousar Lutar. Ousar Vencer. Órgão do Movimento Associativo dos Estudantes de Direito de Lisboa, n.º 7.